ANALISIS STRATEGI PENDIDIKAN KARAKTER DAN DIGITALISASI SEKOLAH DALAM RENSTRA DINAS PENDIDIKAN DAN KEBUDAYAAN - Revi Adekamisti; Hamengkubuwono; Jumira Warlizasusi; Irwan Fathurrochman (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to analyze the character education and school digitalization strategies outlined in the Strategic Plan (Renstra) of the Department of Education and Culture of Kepahiang Regency for the period 2021–2026. The method used is document analysis of the Renstra, which serves as a medium-term policy framework for the development of the education sector. The analysis results indicate that the character education strategy focuses on the integration of character values into the curriculum, continuous teacher training, and the reinforcement of extracurricular activities that support the development of students' personalities. Meanwhile, the school digitalization strategy includes the development of information and communication technology (ICT) infrastructure, the enhancement of digital competencies among teachers and education personnel, and the integration of technology into an adaptive and innovative learning process. These two strategies are mutually reinforcing in the effort to improve the overall quality of education in Kepahiang Regency, with the hope of addressing 21st-century challenges and strengthening the competitiveness of the younger generation at both local and global levels